The Influence of Personality Traits on Postpartum Depression: A Systematic Review Based on the NEO-FFI Scale - Oana Neda-Stepan; Cătălina Giurgi-Oncu; Andreea Sălcudean; Elena Bernad; Brenda-Cristiana Bernad; Virgil Radu Enătescu (Diseases, 2024)
Postpartum depression (PPD) is a significant global health concern with profound implications for mothers, families, and societies. This systematic review aims to synthesize current research findings to understand better how personality traits, as assessed by the NEO Five-Factor Inventory (NEO-FFI), contribute to the development and progression of PPD. Conducted in January 2024, this review searched major databases like PubMed, PsycINFO, and Scopus up to December 2023, focusing on the NEO-FFI’s role in evaluating PPD. Following PRISMA guidelines, studies were selected based on strict criteria, including the exclusive use of NEO-FFI for personality assessment and a focus on postpartum women. A total of seven studies were included after a rigorous two-step screening process, and their data were qualitatively synthesized. The review covered a total of 4172 participants, with a prevalence of clinically significant postpartum depression symptoms ranging from 10.6% to 51.7%. Notably, Neuroticism emerged as a significant predictor of PPD, with odds ratios ranging from 1.07 (95% CI: 0.96–1.20) in some studies to as high as 1.87 (95% CI: 1.53–2.27) in others. In contrast, traits like Extraversion and Conscientiousness generally showed protective effects, with lower scores associated with reduced PPD risk. For instance, Extraversion scores correlated negatively with PPD risk (Beta = −0.171) in one study. However, the impact of other traits such as Openness and Agreeableness on PPD risk was less clear, with some studies indicating negligible effects. The review highlights Neuroticism as a consistent and significant predictor of PPD risk, with varying impacts from other personality traits. The findings suggest potential pathways for targeted interventions in maternal mental health care, emphasizing the need for comprehensive personality evaluations in prenatal and postnatal settings.